MicroRNA-related polymorphisms and non-Hodgkin lymphoma susceptibility in the Multicenter AIDS Cohort Study. (December 2016) - Peckham-Gregory, Erin C.; Thapa, Dharma R.; Martinson, Jeremy; Duggal, Priya; Penugonda, Sudhir; Bream, Jay H.; Chang, Po-Yin; Dandekar, Sugandha; Chang, Shen-Chih; Detels, Roger; Martínez-Maza, Otoniel; Zhang, Zuo-Feng; et al.
Highlights: This study generated data on novel miRNA-related susceptibility loci for AIDS-NHL. DDX20 rs197412 in a miRNA biogenesis gene increases AIDS-NHL risk and miRNA serum levels. HIF1A rs2057482 creates a miRNA-196a2 binding site and influences AIDS-NHL risk. These results suggest biomarkers and miRNA pathways for AIDS-NHL risk stratification. Abstract: Background: MicroRNAs, small non-coding RNAs involved in gene regulation, are implicated in lymphomagenesis. We evaluated whether genetic variations in microRNA coding regions, binding sites, or biogenesis genes (collectively referred to as miRNA-SNPs) were associated with risk of AIDS-associated non-Hodgkin lymphoma (AIDS-NHL), and serum levels of four lymphoma-related microRNAs. Methods: Twenty-five miRNA-SNPs were genotyped in 180 AIDS-NHL cases and 529 HIV-infected matched controls from the Multicenter AIDS Cohort Study (MACS), and real-time polymerase chain reaction was used to quantify serum microRNA levels. Adjusted odds ratios (ORs) estimated using conditional logistic regression evaluated associations between miRNA-SNPs and AIDS-NHL risk. A semi-Bayes shrinkage approach was employed to reduce likelihood of false-positive associations. Adjusted mean ratios (MR) calculated using linear regression assessed associations between miRNA-SNPs and serum microRNA levels. Results: DDX20 rs197412, a non-synonymous miRNA biogenesis gene SNP, was associated with AIDS-NHL risk (OR = 1.34 per minor allele; 95% CI: 1.02–1.75), and higher miRNA-222 serum levels nearing statistical significance (MR = 1.21 per minor allele; 95% CI: 0.98–1.49). MiRNA-196a2 rs11614913 was associated with decreased central nervous system (CNS) AIDS-NHL (CT vs. CC OR = 0.52; 95% CI: 0.27–0.99). The minor allele of HIF1A rs2057482, which creates a miRNA-196a2 binding site, was associated with systemic AIDS-NHL risk (OR = 1.73 per minor allele; 95% CI: 1.12–2.67), and decreased CNS AIDS-NHL risk (OR = 0.49 per minor allele; 95% CI: 0.25–0.94). Conclusions: This study suggests that a few miRNA-SNPs are associated with AIDS-NHL risk and may modulate miRNA expression. These results support a role for miRNA in AIDS-NHL and may highlight pathways to be targeted for risk stratification or therapeutics.